2012
DOI: 10.1007/s00586-012-2542-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of complications in neuromuscular scoliosis surgery: a literature meta-analysis from the past 15 years

Abstract: Purpose Our objectives were primarily to review the published literature on complications in neuromuscular scoliosis (NMS) surgery and secondarily, by means of a meta-analysis, to determine the overall pooled rates (PR) of various complications associated with NMS surgery. Methods PubMed and Embase databases were searched for studies reporting the outcomes and complications of NMS surgery, published from 1997 to May 2011. We focused on NMS as defined by the Scoliosis Research Society's classification. We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
119
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 80 publications
8
119
1
2
Order By: Relevance
“…23,29,31 The SRS M&M database has produced somewhat lower results of complications in the past when compared with other databases such as the NSQIP, but the studies that demonstrated these differences still validated the SRS M&M as a resource. 12,21,33,34,39 The differences in our results are possibly due to an underreporting of medical complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,29,31 The SRS M&M database has produced somewhat lower results of complications in the past when compared with other databases such as the NSQIP, but the studies that demonstrated these differences still validated the SRS M&M as a resource. 12,21,33,34,39 The differences in our results are possibly due to an underreporting of medical complications.…”
Section: Discussionmentioning
confidence: 99%
“…3,8,12,14,30,[33][34][35] One subgroup of scoliosis, neuromuscular scoliosis, has been associated with complication rates of more than 35% in recent studies, consistently higher than those of idiopathic scoliosis. 23,29,31 Neuromuscular scoliosis is an irregular spi-ABBREVIATIONS DVT = deep venous thrombosis; IONM = intraoperative neuromonitoring; M&M = Morbidity and Mortality; MRSA = methicillin-resistant Staphylococcus aureus; MSSA = methicillin-sensitive Staphylococcus aureus; NSQIP = National Surgical Quality Improvement Program; PE = pulmonary embolism; SRS = Scoliosis Research Society; SSI = surgical site infection; VTE = venous thromboembolism. …”
mentioning
confidence: 99%
“…Complications have been reported to affect many body systems including respiratory, gastrointestinal and neurological. In a recent meta-analysis of complications following surgery for neuromuscular scoliosis, pulmonary complications were found to be most common (22.7%), followed by implant complications (12.5%) and infections (10.9%) (88). The authors suggested age at the time of surgery (<13 years) was associated with higher rates of neurological (15.1% compared to 3%) and pseudarthrosis (11.6% compared to 1.7%) (88).…”
Section: Complicationsmentioning
confidence: 99%
“…In a recent meta-analysis of complications following surgery for neuromuscular scoliosis, pulmonary complications were found to be most common (22.7%), followed by implant complications (12.5%) and infections (10.9%) (88). The authors suggested age at the time of surgery (<13 years) was associated with higher rates of neurological (15.1% compared to 3%) and pseudarthrosis (11.6% compared to 1.7%) (88). No explanation of this association was offered, however younger, smaller patients may cause an increased difficulty in placement of instrumentation therefore increasing risk of neural injury and failure of fusion.…”
Section: Complicationsmentioning
confidence: 99%
“…3,5,6 The secondary complications of neuromuscular scoliosis often include pelvic obliquity, skin breakdown, pulmonary compromise, and functional decline. 2 Because of the potentially devastating consequences of neuromuscular scoliosis on body functions and the high rate of complications associated with spine surgery for neuromuscular scoliosis, 7 treatment to prevent or slow the progression of neuromuscular scoliosis is a primary focus of the longitudinal care of children with SCI.…”
mentioning
confidence: 99%